2015
DOI: 10.3233/jcb-15004
|View full text |Cite
|
Sign up to set email alerts
|

Mechanics of the red blood cell network

Abstract: Changes in the microstruture of blood caused by the red blood cell aggregation phenomenon affect the mechanical properties of the fluid. This fact has been extensively investigated in the past and it has been verified that the formation of rouleaux (the characteristic coin-pile like structures) and aggregates at low shear rates affect the flow and as a consequence the viscosity of the fluid is elevated. At physiological red blood cell concentrations and at low shear rates, however, in addition to rouleaux and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…Blood has a pronounced non-Newtonian character, primarily attributed to aggregation, disaggregation, deformation, orientation, and migration of the erythrocytes [ 5 , 6 , 7 , 8 , 9 ]. Our model encompassed all the crucial aspects of blood rheology, including yield stress [ 10 , 11 ], thixotropic effects [ 12 , 13 , 14 ], viscous dissipation, and elasticity, which are associated with the aggregation/disaggregation of the erythrocytes [ 15 , 16 ]. The latter features are accompanied by the introduction of a microstructural state indicator that dynamically responds to the stresses currently present in the system.…”
Section: Introductionmentioning
confidence: 99%
“…Blood has a pronounced non-Newtonian character, primarily attributed to aggregation, disaggregation, deformation, orientation, and migration of the erythrocytes [ 5 , 6 , 7 , 8 , 9 ]. Our model encompassed all the crucial aspects of blood rheology, including yield stress [ 10 , 11 ], thixotropic effects [ 12 , 13 , 14 ], viscous dissipation, and elasticity, which are associated with the aggregation/disaggregation of the erythrocytes [ 15 , 16 ]. The latter features are accompanied by the introduction of a microstructural state indicator that dynamically responds to the stresses currently present in the system.…”
Section: Introductionmentioning
confidence: 99%
“…The aforementioned studies used image analysis techniques for the characterisation of aggregate size, as they provide unequivocal data [16]. However, there are certain limitations in the use of image analysis for aggregate characterisation, with the main one been the RBC concentration, which affects the image quality due to high light absorption.…”
Section: Introductionmentioning
confidence: 99%
“…their carboxyl and hydroxyl groups, osmolality and chemotoxicity [6,7]. Several studies revealed enormous differences in the RCM-induced formation of echinocytes [1,11,13,16,17,[20][21][22]28] and also in the aggregability of erythrocytes [10] which also might influence the microcirculatory blood flow [14,15]. These differences could be due to variations in the loss of constituents of the membrane cytoskeleton (e.g.…”
Section: Introductionmentioning
confidence: 99%